1995
DOI: 10.1159/000203981
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Anemia in a Patient with Subacute Bacterial Endocarditis Due to <i>Streptococcus sanguis</i>

Abstract: We describe a case of hemolytic anemia with subacute bacterial endocarditis due to Streptococcus sanguis. The major hematological features of the patient were a normocytic anemia with reticulocytosis, an elevation of serum lactate dehydrogenase, and a marked reduction of serum haptoglobin. All these signs of hemolytic anemia fluctuated in parallel with changes in inflammatory activity and were dramatically improved by the administration of benzylpenicillin, suggesting that the infection with S. sanguis itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hemolytic anemia has been reported in only a few previous. [2][3][4][5][6][7] Maeda et al reported a 65-year-old female with hemolysis associated with streptococcal endocarditis of the mitral valve. 2 That patient had an underlying obstructive hypertrophic cardiomyopathy with a 115-mmHg pressure gradient in the left ventricular outflow tract and a moderate mitral regurgitation due to mitral valve prolapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemolytic anemia has been reported in only a few previous. [2][3][4][5][6][7] Maeda et al reported a 65-year-old female with hemolysis associated with streptococcal endocarditis of the mitral valve. 2 That patient had an underlying obstructive hypertrophic cardiomyopathy with a 115-mmHg pressure gradient in the left ventricular outflow tract and a moderate mitral regurgitation due to mitral valve prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…Inada et al also demonstrated improvement of hemolytic anemia after antibiotic therapy in a patient with Streptococcus sanguis endocarditis. 5 In contrast, the patient with staphylococcal endocarditis involving the tricuspid valve due to drug abuse, reported by Gradon et al, required surgical removal of the vegetations for control of the hemolytic process. 6 In an infant with hemolysis reported by Hsu et al, the right ventricle was occupied by a huge fungal ball and there were spherocytes, splenomegaly, and a positive direct Coombs test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia has been shown to frequently accompany infective endocarditis (1). Although rare, there have been reports of hemolytic anemia associated with native valve infective endocarditis (2)(3)(4)(5)(6)(7)(8)(9). In addition, some patients with infective endocarditis do not become febrile.…”
Section: Introductionmentioning
confidence: 99%
“…Although S. sanguinis is a normal inhabitant of the mouth in healthy humans, it may cause subacute bacterial endocarditis in patients even without structurally abnormal heart valves. 15 In pediatrics, viridans streptococcus (including S. sanguinis ) sepsis was mostly described in patients with cancer receiving chemotherapy. 16 Our patient was not immuno-compromised, was not at risk of implantable venous port-associated bloodstream infections, and had not received specific procedures of recent dental cleaning or surgery.…”
Section: Discussionmentioning
confidence: 99%